ANALISIS PERHITUNGAN PAJAK PENGHASILAN (PPh) PASAL 21 ATAS GAJI KARYAWAN PADA CV. IDEAS 03 ENGINEERING DI SAMARINDA (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2016)
The problem of this research is Do the calculations, deposit and reporting of income tax on salaries of employees Article 21 Cv Ideas 03 Engginering in Samarinda in accordance with Law No. 36 of 2008. The purpose of this study was to calculate the amount of income tax Article 21 based on the employee's salary CV.Ideas 03 Engineering in Samarinda period from January to December, 2014 and calculates the calculation procedure, deposit and reporting of income tax article 21 employees CV.Ideas 03 Engineering in Samarinda. Based on the results of calculation of Income Tax of Article 21 on the CV. Ideas 03 Engineering in Samarinda, based on the analysis and calculations have been carried out on the CV. Ideas 03 Engineering in Samarinda, based on the analysis and calculations have been carried out on the salary / income of employees at 03 CV.Ideas Engineering in the tax period January - December 2014 result Income Tax Article 21 amounting to 4.399.950 and by Law No. 36 in 2008 is 2.303.813, so the calculation of income tax of Article 21 of the Employee Salary CV.Ideas 03 Engineering in Samarinda is not compliance with tax laws and regulationsKeywords: Calculation,depositing, reporting, Income Tax Article 21 , The Tax of Law and Salary